Metabolism and Epigenetic Interplay in Cancer: Regulation and Putative Therapeutic Targets - Miranda-Gonçalves, Vera; Lameirinhas, Ana; Henrique, Rui; Jerónimo, Carmen (Frontiers in Genetics, 2018)
Alterations in the epigenome and metabolism affect molecular rewiring of cancer cells facilitating cancer development and progression. Oncogene-driven metabolic reprogramming modifies the epigenetic landscape through DNA and histone modification enzymes modulation. Conversely, epigenetic mechanisms regulate the expression of metabolism-related genes, promoting the well-known metabolic reprogramming of cancer cells and, consequently, changing the metabolome. Thus, epigenetic-metabolomic interplay plays a critical role in tumorigenesis by co-ordinately sustaining cell proliferation, metastasis and pluripotency. In this review we emphasize the importance of tumour metabolites in the activity of most chromatin-modifying enzymes and their underlying role in tumorigenesis. Furthermore, we highlight promising molecular targets in tumour metabolism as well as in the epigenetic machinery, focusing on development of small molecules or biologic inhibitors that counteract the epigenomic-metabolic interplay in cancer.